(untitled) (Indian Journal of Arid Horticulture, 2013)
Soil test crop response correlation studies were conducted with vegetable guar under integrated plant nutrition system (STCR-IPNS) in Torripsamments of Rajasthan during Kharif 2003. Fertilizer adjustment equations under IPNS were formulated for vegetable guar following Ramamoorthy’s inductive-cum targeted yield model. The nutrient requirement for producing one quintal of veg. cluster bean was found to be 6.80, 1.17 and 4.62 kg of N,P O and K O, 2 5 2 respectively. The per cent nutrient utilization efficiencies from soil and fertilizer nutrients were found to be 72.72 and 59.62 for N, 33.93 and 17.73 for P O and 45.34 and 50.10 for K O, respectively. Like wise the percent nutrient utilization 2 5 2 efficiency from farmyard manure (FYM) was 200 for N, 32.66 for P O and 137.92 for K O, respectively. In STCR-IPNS 2 5 2 technology, the fertilizer doses are tailored to the requirements of specific yield targets of veg. cluster bean taking into account the contribution from soil, fertilizers and organics.